Influence of sex, age and length of service on scientific productivity of medical research institution staff - O. M. Drapkina; E. A. Poddubskaya; V. B. Rozanov; L. G. Gasanova (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To assess the influence of sex, age and length of service on scientific productivity (h-index in the RSCI, Scopus and Web of Science) of researchers of the National Medical Research Center for Therapy and Preventive Medicine.Material and methods. The study sample was formed from the staff of the National Medical Research Center for Therapy and Preventive Medicine and consisted of scientists of various ranks. The study included 147 people (women, 103; men, 44); Information was collected on their age, education, length of service, academic degree, the position held and author-level metrics  — the h-index, obtained from three abstract and citation databases  — RSCI, Scopus and Web of Science. All study participants were divided into groups by sex and age categories — young (≤39 years), middle-aged (men, 40-60 years; women, 40-55 years) and older (men >60 years old; women >55 years).Results. Analysis showed that 70,1% of the research team consists of women; 60%  — young and middle-aged scientists, and 40%  — older people. Among male researchers, compared with women, there are more doctors of science and high h-index values in the RSCI, Scopus and Web of Science. H-index value in the RSCI among male researchers is 47,3% due to the age and work duration at the National Medical Research Center for Therapy and Preventive Medicine, and among female researchers, 42,8% due to academic degree and length of service. The h-index in Scopus in men is influenced by age, in women  — by the presence of an academic degree, which explain, respectively, 19,7 and 18,1% of its variability. H-index value in the Web of Science in men is associated with the work duration, while in women, with an academic degree and length of service, which explain, respectively, 24,4 and 21,1% of its variance.Conclusion. Women and young and middle-aged scientists prevail in research team pattern of the National Medical Research Center for Therapy and Preventive Medicine. However, male researchers make a more significant contribution to scientific productivity, assessed by the h-index in the RSCI, Scopus and Web of Science. Age and length of service have the greatest influence on scientific productivity for male researchers, while for women — presence of academic degree and length of service. It is necessary to continue research on the study of individual, motivational and institutional factors affecting the scientific productivity.